1997
DOI: 10.1002/(sici)1097-0029(19970915)38:6<643::aid-jemt8>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural aspects of human gallbladder epithelial cells in cholelithiasis: Production of anionic mucus

Abstract: The surface epithelium of 28 gallbladders removed during elective cholecystectomies and pathology collection was studied ultrastructurally. Focusing on 10 of the 28 cases that were diagnosed as cholecystitis, we found that the epithelium displayed numerous apical mucous granules and bulging apical apices. Mucous granule changes included 1) hyperproduction of secretory granules of neutral type containing an electron-dense proteinaceous spherule, similar to that described in other mucus-producing glands of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…However, a small number of specimens deemed to be of more complex pathology displaying cholesterolosis and carcinomas allowed us to describe specific subcellular changes in the mucous vesicles of the human gallbladder [4,5] and supplemented other reports also based on human samples [6^8]. During cholelithiasis, inflammatory changes were observed with acute cholecystitis, but many of them, diagnosed as short-term to chronic cholecystitis, mainly appear with epithelial changes in the form of qualitative mucus changes [3,9]. These observations concur with earlier observations [10^15].…”
mentioning
confidence: 80%
“…However, a small number of specimens deemed to be of more complex pathology displaying cholesterolosis and carcinomas allowed us to describe specific subcellular changes in the mucous vesicles of the human gallbladder [4,5] and supplemented other reports also based on human samples [6^8]. During cholelithiasis, inflammatory changes were observed with acute cholecystitis, but many of them, diagnosed as short-term to chronic cholecystitis, mainly appear with epithelial changes in the form of qualitative mucus changes [3,9]. These observations concur with earlier observations [10^15].…”
mentioning
confidence: 80%
“…Their findings suggest that chronic inflammatory changes can occur in the gall bladder mucosa prior to appearance of macroscopic stones. [27] -Lee KT, Sheen PC, Y: E, Erlia Y et al in 1998 studied mucin content in gall bladder with brown pigment stones or combination stones. Gall bladder mucin itself has been recognised to play the important role in gall stones development.…”
Section: Imentioning
confidence: 99%
“…[26] How ever in black pigment stones which are devoid of cholesterol, the interaction of mucin, calcium and bilirubin is the sole mechanism for cholelithiasis. [27,29,30] In this context the role of acid mucins, especially sulfomucins become more important to the formation of black pigment stones. [27] In present study of the mucin histochemistry of cholelithiasis gall bladder it was found that sulfomucins were predominant in supranuclear region (Brownish blue by PAS-AB).…”
Section: 5"mucin Histochemistry In Cholelithiasis Gallbladder"fig12"mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies the ultrastructure of the normal mucosa, ultrastructural observations regarding mucoid material and lipids have been outlined [2,3,4,5,6]. It was early evident that alterations in the cholecystocytes were only identified with ultrastructural examinations.…”
mentioning
confidence: 99%